2019
DOI: 10.18203/2349-3291.ijcp20193733
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of fever and febrile illness among parents of under five children

Abstract: Background: Fever in children is the commonest cause for outpatient and inpatient admissions in the health care setup. Though most fever episodes are benign with self-limiting course, it is often a reason for anxiety and concerning for parents. The aim of the study was to assess the parental knowledge, attitude and practice regarding fever in children under five years of age.Methods: A cross-sectional question based survey, conducted in the pediatric department of a peripheral hospital in Pune, Maharashtra fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 15 publications
4
7
0
Order By: Relevance
“…In our study 98 (98%) parent's used medications to bring down the fever. Majority of parents 56 (56%) in this study, claimed to have derived this information from doctors which is similar to the study done by Mallick [8] in which Majority of parent's (98.3%) agreed to have visited a doctor for fever. This is similar to our study.Maximum number of parents 43(43%) in this study feared seizures as the complication of fever.…”
Section: Discussionsupporting
confidence: 84%
“…In our study 98 (98%) parent's used medications to bring down the fever. Majority of parents 56 (56%) in this study, claimed to have derived this information from doctors which is similar to the study done by Mallick [8] in which Majority of parent's (98.3%) agreed to have visited a doctor for fever. This is similar to our study.Maximum number of parents 43(43%) in this study feared seizures as the complication of fever.…”
Section: Discussionsupporting
confidence: 84%
“…23 The level of parents' literacy is an important factor contributing to the overall health care of children and uncompleted education might lead to insufficient knowledge and unsatisfactory practices. 20 The majority of the respondents of the current study came from urban areas (87%) which go with the study by Abdinia and colleagues. 17 In contrast, other studies revealed that the maximum number of participants resided in rural areas.…”
Section: Discussionsupporting
confidence: 66%
“…Accurate knowledge of the caregivers is therefore crucial which could affect the attitude and performance while initial monitoring and management of a febrile child. 20 In this regard, we investigated the level of knowledge and practice of the Bangladeshi parents or primary caregivers towards childhood fever, using a self-administered questionnaire. In the present study, most of the participants were mothers (96%), as fathers were mostly available in their respective working places and could not accompany their wives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations